Characterization of factors that influence on milk production in usufructuaries farms of Consolación del Sur municipality, Pinar del Río - Alonso, A. C.; Torres, Verena; Herrera-Hernández, J. A.; Iriban, C. A.; Chongo, Bertha (Cuban Journal of Agricultural Science, 2020)
The Statistical Model of Impact Measurement (MEMI) was applied to evaluate the factors that determine the efficiency of milk production in farms of farmers from the cooperative and farmer sector, usufructuaries from Camilo Cienfuegos Genetic Livestock Enterprise, Consolación del Sur municipality, Pinar del Río, Cuba. The study covered 74 usufructuaries, associated with six productive forms or Credit and Service Cooperatives from Consolación del Sur municipality. The evaluated indicators were: information of farmers (9 variables), information of usufruct farms (17 variables), information of the economic area of each productive form to which they are associated (4 variables) and others generated (5 variables). The principal component analysis of the studied variables showed that the first five components explained 81.00 % of the total variability of the data. The first main component was related to herd and production; the second with efficiency indices in milk production, the third with infrastructure and the fourth grouped adopted technologies. While, the fifth, and last, was related to areas and yields. The results confirmed that the adopted technologies have a great influence on the productive performance and the efficiency achieved by the farm. The negative impacts show the need to reorient the work of managers and usufructuaries to undertake actions, in which training prevails accompanied by a strong movement of agricultural extension, which transfers existing technologies to the milk-producing sector. This would cause a favorable transformation in the productive yields that are currently being achieved. Key words: agrarian extension, productive forms, impact index, farmers, technologies.